Investigation of Population Changes and Determination of the Bean Pod Borer Helicoverpa armigera (Lepidoptera:Noctuidae) Peak in Bean Phaseolus vulgaris Linnaeus Fields by Pheromone Traps - Sedighe Ashtari (پژوهش‌های حبوبات ایران, 2024)
Introduction beans Phaseolus vulgaris Linnaeus, is one of the most important legumes cultivated in many countries around the world. According to statistics published by the Ministry of Agriculture, the cultivated area of beans in Iran is 91798 ha with an average yield of 2307 kg.ha-1. In Markazi province, the cultivated area of beans is 13401 ha with an average yield of 2786 kg.ha-1, making it one of the major bean-growing regions in the country. The bean pod borer, scientifically known as Helicoverpa armigera Hufn. (Lep.Noctuidae), is one of the important pests. Materials and Methods To address the damage caused by this pest to bean crops, a project was conducted to study changes in the population of adult insects and larvae over two years (2022 and 2023). In each of the two study areas (Milajerd and Khomein), two infected farms (approximately one hectare each) were selected (a total of 4 farms), and 3 delta traps were placed in each farm in a triangular pattern and 100 meters apart. To eliminate edge effects for trap installation, traps were placed 5 meters inside the field and then installed. Traps were placed at a height equal to the tallest part of the plant using wooden stakes. This height was maintained throughout the experiment. Traps were installed before flowering and collected prior to crop harvest. Insects caught in pheromone traps were collected and counted weekly. To monitor larvae, two additional infested farms (each approximately one hectare and different from the farms where traps were installed) were selected. From each farm, 30 plants were randomly chosen during mid-flowering, and the number of larvae was counted every two weeks until harvest. To assess the extent of damage, 30 plants were selected from each farm after crop maturation and before harvest. For each plant, all healthy and damaged pods were identified, and the number of holes per pod, the damaged seeds in each pod, and the total seeds per pod due to pest activity were counted. Finally, the percentage of infection was estimated. Results and Discussion The findings from the pheromone trap study showed that, over the two-year period, Khomein county had a higher pest population than Milajerd. In the first year in Khomein county, the peak population was observed on Mordad 1 (July 23) in all three traps across both fields. In the second year, on the seventh of Mordad (July 29), the peak population of night moths occurred in Khomein county. In Milajerd county, the peak of moth capture happened in the first and second years on the sixteenth of Mordad (August 7) and the eleventh of Mordad (August 2) respectively. Examination of larval populations indicated that the peak of larval (First and second instar larvae) populations also occurred two weeks after the peak of night moth capture. Since local red and white bean varieties are more cultivated in Khomein and Milajerd counties respectively, the contamination level of red beans in Khomein compared to white beans in Milajerd has been higher. Therefore, to prevent pest spread, it is recommended that in areas with high contamination, cultivation of local white bean varieties should be prioritized over local red bean varieties. The investigation of the distribution and damage level of bean pod borer in important bean-growing areas of Markazi province over two years in five bean-growing regions (Arak, Khomain, Shazand, Milajerd, and Khondab) showed that Khomain and Khondab had the highest and lowest infestation rates, respectively. Red pods showed more sensitivity to this pest compared to green and white pods. In this study, the highest population of bean pod borer larvae was recorded in the mid-flowering stage (Ashtari et al., 2022). The results of this research align with findings on the sensitivity of red bean pods and the timing of bean pod borer population emergence. Studies have shown that the optimal timing for chemical control of chickpea pod borers is when the maximum number of small larvae appears, typically coinciding with the mid-flowering and early pod formation stages (Shafaghi et al., 2022). Conclusions Considering that the largest population of bean pod borer larvae was about two weeks after the peak of the flight, therefore, it is recommended that if the population of this pest is high and there is a need for chemical control, it should be done about two weeks after the peak of the flight. Also, in order to reduce the percentage of pollution, it is recommended that if possible, farmers prioritize the cultivation of white beans over Chiti and red beans.